Eye Sight - A Bull’s Eye Target of COVID-19 - Maham Arshad, Ayesha Ellahi, Fahad Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the effect of COVID-19 on eye sight due to increase screen time in undergraduate students of medical school. Study design: Cross-sectional study. Place and duration of study: This survey was carried out from October 2022 to December 2022 in Army Medical College Rawalpindi. Questionnaires were filled in person and also online-based platform was used to distribute the e-questionnaire, developed using the Google Form. The participants were asked to share the e-questionnaire with their friends using Facebook and Messenger. Methods: Participants were selected for the study using non-probability consecutive sampling. College students of 20-25 years were included in the study. Sample size was 400 according to a study done internationally. Participants with comorbidities (cataract, glaucoma) were excluded from study. Participants having (trouble concentrating on things such as reading the newspaper, books or watching television) were included in the study. Digital eye strain was calculated using validated computer vision syndrome (CVS-Q) questionnaire to measure the symptoms such as eye fatigue, headache, blurred vision, double vision, itching eyes, dryness, tears, eye redness and pain, excessive blinking, feeling of a foreign body, burning or irritation, difficulty in focusing for near vision, feeling of sight worsening, and sensitivity to light. Qualitative data was analyzed using Chi square test. Results A total number of 470 responses were recorded, out of which 257 (54.7%) were males and 213(45.3%) were females. In our study, the most common symptom was headache, affecting 58.1% of the population before COVID 19 which has increased to 83.2% and the P value is less than 0.001.Theother symptoms which also showed P value less than 0.001 were blurred vision while using digital device, irritated or burning eyes, dry eyes and sensitivity to bright light. Conclusion The practical implication of the study is to create awareness among general population about COVID, that eye sight is Bull`s Target to be affected by it and simple preventing measures can be taken. The purpose of this study is to limelight the importance that during COVID 19 lockdown the excessive use of digital devices and their cons on the ocular health among future health care workers. Key words: Eye sight, Undergraduate students, computer vision syndrome, video display terminals